Effects of Ukrain on intestinal apoptosis caused by ischemia-reperfusion injury in rats - Akcılar, Raziye (Int J Clin Exp Med, 2015)
Background: To investigate the antiapoptotic effect of Ukrain on intestinal lesion induced by mesenteric ischemia-reperfusion (I/R) injury. Methods: Male Sprague-Dawley rats were divided into three groups: laparotomy (L), I/R, and Ukrain and I/R (U + I/R). In the U + I/R group, Ukrain (7 mg/kg) was given by intraperitoneal at the beginning of the study. 1 h after ukrain application, ischemia was induced for 30 minutes, and reperfusion was subsequently allowed for 120 minutes in the I/R and U + I/R groups. Rats were sacrificed at the end of reperfusion and intestinal tissues were collected for biochemical and molecular examination. Intestinal tissues caspase 3 protein were assayed. Serum Bcl-xL and iNOS were measured. The expression level of caspase-3, Bcl-xL and iNOS in intestinal tissue of rats were detected by reverse transcription-polymerase chain reaction (RT-PCR). Results: Levels of serum iNOS and mRNA expression were increased in the I/R and decreased in the U + I/R group. In addition, levels of the proapoptotic gene caspase-3 protein and mRNA expression were increased in the I/R and decreased in the U + I/R group. Levels of the antiapoptotic gene Bcl-xL serum and mRNA expression were increased in the U + I/R group. Conclusions: Ukrain can reduce the ischemia-reperfusion injury in the intestinal tissue by inhibiting the cell apoptosis. The mechanism may be correlated with increased Bcl-xL mRNA expressions and decreased mRNA expressions of Caspase-3 and iNOS.